Pengembangan Produk Baru dan Model-Model Evaluasi Produk Baru - Nurilda Wardiah (Jurnal Manajemen Maranatha, 2003)
This writing is likely to discuss about process, approaches,interrupting, and models of new product evaluation. The effective strategies and extract of new product development are determining factors of firm's survival. It is not an easy role to perform, for it needs lots of tries, time and firm's resources ability - include risk and failure cost. New product development starts from identification of consumer's needs and wants until commercialization, include launching and interrupting new product. Being done well, each step insuch development is hardly required to evaluate before go to next step. There are some new product development models available to be extract. The use of models depends on our goal. For example, products type data available, environment, time, and diagnostic of information. In evaluating new product, managers can use those models. This discuss about new product development expect to be reviewed by manager in doing their dutyKeywords : New product development. product launch andelimination, new product evaluation. and new product evaluation models